Periodic assessment of antenatal and post natal serum endothelin-1 and nitric oxide levels in hypertensive disorders of pregnancy - Ismawi, Hidayatul Radziah; Abdul Razaq, Tariq; Mohd Zainudin, Maizura; Jamani, Nurjasmine Aida (Kulliyyah (Faculty) of Medicine, International Islamic University Malaysia, 2018)
Hypertensive Disorder of Pregnancy (HDP) is an independent risk factor of cardiovascular (CVS) disease with persistent endothelial dysfunction, that occurs after the initial insult during pregnancy and persists post partum postulated to be the pathophysiology. Endothelin-1 (ET-1), a potent vasoconstrictor, has been identified as a pivotal mediator in both essential hypertension and HDP. Disturbances in Nitric Oxide (NO) bioavailability found in endothelial dysfunction may increase susceptibility to cardiovascular diseases such as hypertension.